Cardiac troponin release following coronary artery bypass grafting: mechanisms and clinical implications. (7th November 2022) - Heuts, Samuel; Gollmann-Tepeköylü, Can; Denessen, Ellen J S; Olsthoorn, Jules R; Romeo, Jamie L R; Maessen, Jos G; van 't Hof, Arnoud W J; Bekers, Otto; Hammarsten, Ola; Pölzl, Leo; Holfeld, Johannes; Bonaros, Nikolaos; et al.
Abstract: The use of biomarkers is undisputed in the diagnosis of primary myocardial infarction (MI), but their value for identifying MI is less well studied in the postoperative phase following coronary artery bypass grafting (CABG). To identify patients with periprocedural MI (PMI), several conflicting definitions of PMI have been proposed, relying either on cardiac troponin (cTn) or the MB isoenzyme of creatine kinase, with or without supporting evidence of ischaemia. However, CABG inherently induces the release of cardiac biomarkers, as reflected by significant cTn concentrations in patients with uncomplicated postoperative courses. Still, the underlying (patho)physiological release mechanisms of cTn are incompletely understood, complicating adequate interpretation of postoperative increases in cTn concentrations. Therefore, the aim of the current review is to present these potential underlying mechanisms of cTn release in general, and following CABG in particular ( Graphical Abstract ). Based on these mechanisms, dissimilarities in the release of cTnI and cTnT are discussed, with potentially important implications for clinical practice. Consequently, currently proposed cTn biomarker cut-offs by the prevailing definitions of PMI might warrant re-assessment, with differentiation in cut-offs for the separate available assays and surgical strategies. To resolve these issues, future prospective studies are warranted to determine the prognostic influence of biomarker release in general and PMI in particular. Graphical Abstract: Graphical Abstract Possible mechanisms of cardiac troponin release and their mechanistic causes in patients undergoing CABG (Barry van Varik, Pulse Medical Art). CABG, coronary artery bypass grafting; cTnI, cardiac troponin I; cTnT, cardiac troponin T; LV, left ventricular. Audio Abstract: